2009
DOI: 10.2134/agronj2008.0179s
|View full text |Cite
|
Sign up to set email alerts
|

Deficit Irrigation Optimization of Cotton with AquaCrop

Abstract: Given the current pressures to reduce irrigation water use, it is important to optimize the use of water in irrigated agriculture. Th is work was aimed at determining the optimum level of applied irrigation water (AIW) for cotton (Gossypium hirsutum L.) production in southern Spain under several climatic and agricultural policy scenarios. To generate the yield response to variations in AIW, we used the FAO crop water productivity (WP) model, AquaCrop. Model calibration and validation using four experiments con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(66 citation statements)
references
References 42 publications
1
63
0
2
Order By: Relevance
“…The results of the economic model demonstrated that maximum profit from quinoa production can be achieved with less irrigation water than required for maximum quinoa yield in all type of climate scenarios, and that prof it differences between rainfed and irrigated quinoa are greater in dry and very dry years. Also, as it was found by other studies García-Vila et al, 2009;Pérez-Pérez et al, 2010), the study showed that product price is one of the main forces to drive the use of irrigation for improving crop productivity.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The results of the economic model demonstrated that maximum profit from quinoa production can be achieved with less irrigation water than required for maximum quinoa yield in all type of climate scenarios, and that prof it differences between rainfed and irrigated quinoa are greater in dry and very dry years. Also, as it was found by other studies García-Vila et al, 2009;Pérez-Pérez et al, 2010), the study showed that product price is one of the main forces to drive the use of irrigation for improving crop productivity.…”
Section: Discussionsupporting
confidence: 56%
“…Economic water productivity can be expressed on the basis of the economic value of the product and water use (Rodrigues & Pereira, 2009), or as in this paper, on the economic value of the product and irrigated water (Playán & Mateos, 2006;García-Vila et al, 2009 …”
Section: Economic Water Productivitymentioning
confidence: 99%
“…The model performance on simulating crop growth and water use has been well tested for a variety of crop types under diverse environmental conditions (e.g. Kumar et al, 2014;Jin et al, 2014;Abedinpour et al, 2012;Mkhabela and Bullock, 2012;Andarzian et al, 2011;Stricevic et al, 2011;Heng et al, 2009;Farahani et al, 2009;García-vila et al, 2009). AquaCrop has been applied in WF accounting at field (Chukalla et al, 2015), river basin (Zhuo et al, 2016a), and national level (Zhuo et al, 2016b) at high spatial resolution.…”
Section: Estimating Consumptive Wf Of Growing a Cropmentioning
confidence: 99%
“…Still, some studies report that model performance declines in estimating some variables in severe water stress environments [1,13]. Although a highlighted feature of the model is the applicability of conservative parameters used in crop simulations (these parameters are reported by Heng et al [8] and Hsiao et al [12] for maize), several researchers observed that model parameterization is essentially site-specific and that important calibrated parameters necessary for accurate simulation must be tested under different climate, soil, cultivars, irrigation methods, and field management to improve the reliability of the simulated results [3,14,15].…”
Section: Introductionmentioning
confidence: 99%